Organization support for cloud computing implementation success in education system: scale development and validity in Delphi - Kassim, Rahimah; Abdul Hamid, Nor Aziati; H.B, Adnan; Mohd Noor, Helmi Adly; Abdul Rahman, Fauziah (Science Publishing Corporation (SPC), 2018)
Cloud computing (CC) support for learning systems has been viewed as one of the most discussed issues that promise to modernize computing by providing visualized resources as a service over the internet. To be stable in cloud computing acquisition requires an education institution to address many of the same concerns they face in implementing an Information System (IS) service. Currently, there is still lack of CC implementation standard and organizational support that impacted VLE system performance. Previous research has reported that the influence of the CC implementation decision depends on the impact of various factors studied. Nonetheless, organizational support is the least factor mentioned especially studies from Malaysia. Thus, the main purpose of this study is to develop a validated scale of organizational support in implementation decision activities towards CC implementation success. In this paper, the Delphi process adopted to measure consensus among nominal group technique (also known as the expert panel). Key methodological issues in using the methods are discussed, along with the distinct contribution of consensus methods as aids to decision making in education service development. The study has adapted stages of proses flow of scale development and validation of measurement items according to legitimate measures in the Delphi technique. The measurement scales formed are based on literature review and field studies conducted to increase the reliability and validity values. Organizational support constructs were divided into top management support, firm size, awareness, Technology Readiness and cost effectiveness. A total of 5 items have been successfully set up for further validation